The Effect of Training and Work Placement on Employee Performance at PT. Cement Baturaja Palembang - Syafitri, Fetty; Agustian, Wiwin (SEIKO : Journal of Management & Business, 2023)
Human resources have an important role for the company, because human resources are a combination of energy, physical, ideas, talents, knowledge, creativity and skills needed to drive the company. An employee's performance is an important starting point for creating company performance. This study aims to determine how much influence Training (X1) and Work Placement (X2) both simultaneously and partially have on Employee Performance (Y) at PT. Semen Baturaja Palembang. The data collection technique uses a questionnaire, the sample in this study is employees of PT. Semen Baturaja Palembang has 64 employees, the analysis technique used in this research is SPSS. The results of this study indicate that Training (X1) and Placement (X2) both simultaneously and partially have a positive and significant effect on Employee Performance (Y) at PT. Semen Baturaja Palembang